Infectious salmon anaemia virus (ISAV) in experimentally challenged Atlantic cod (Gadus morhua) - Grove, S; Hjortaas, M. J; Reitan, L. J; Dannevig, B. H (Archives of virology, 2007)
Juvenile Atlantic cod, Gadus morhua, (6 g) were challenged with infectious salmon anaemia virus (ISAV) either by intraperitoneal (i.p.) injection or by cohabitation with ISA-diseased Atlantic salmon (Salmo salar). Samplings of cod were performed over a period of 45 days and various tissue samples were collected. The presence of ISAV RNA (segment 8) in samples was assessed by both conventional RT-PCR and a competitive quantitative real-time RT-PCR. In the i.p.-challenged group, ISAV RNA was detected in fish from all samplings, i.e. at days 7, 15, 21, 30 and 45 post-challenge. At day 7 post-challenge, all individual fish were positive, and so were the vast majority of individual tissue samples. At later samplings, the fraction of positive brain samples remained high (~75%). In contrast, the positive fraction of other tissues/organs declined during the experiment. Analysis of positive brain samples by a quantitative real-time RT-PCR analysis showed that the level of ISAV RNA increased significantly (~20 times) between days 7 and 30 post-challenge and remained high at day 45, indicating that a replication of ISAV had taken place. ISAV RNA was not detected in any control or cohabitation-challenged fish. No abnormal behaviour, clinical disease or, most notably, mortality was observed in any of the challenge or control groups.